(untitled) (American Journal of Technology and Applied Sciences, 2023)
This article aims to create a non-invasive method for determining glucose levels in diabetes to prevent diabetes. A non-invasive glucometer is aimed at creating a detection concept based on the biophysical parameters of biologically active points. When developing non-invasive fluorescence, experiments were carried out on healthy people and patients with two types of diabetes, confirmed by mathematical and statistical methods that correlate the amount of glucose in the blood and biophysical parameters at biologically active points.